Predictors of Preterm Labor: Case-Control Study - A. V. Sergeeva; O. V. Kovalishena; N. Yu. Katkova; O. I. Bodrikova; I. M. Bezrukova; K. B. Pokusaeva; A. A. Polyakova (Эпидемиология и вакцинопрофилактика)
Background. The problem of preterm labor is currently the most relevant in modern obstetrics, and therefore requires a comprehensive study and application of an integrated approach to its solution. The identification of risk factors for the development of preterm labor, as well as their complex in a pregnant woman, makes it possible to attribute them to a high risk group for the development of preterm labor, which further makes t possible to carry out a number of preventive measures.Aims. The purpose of the study was to identify and test the hypothesis of the relationship between various risk factors and the development of preterm labor.Materials and methods. A retrospective descriptive-estimated selective scientific epidemiological study was conducted according tostatistical reporting forms for the period from 2012 to 2016. The study of the causal relationship of risk factors with the occurrence of preterm labor was carried out using a casecontrol analytical study and calculating the odds ratio (OR) with 95% confidence intervals (CI) using the «Epi InfoTM» program.Results and conclusions. The study period was characterized by minor changes in the rate of preterm labor in the Nizhny Novgorod region. The average long-term figure was 5.0%. The level of preterm birth in the Nizhny Novgorod region was 1.3 times higher than in the Russian Federation. The role of the following risk factors in the occurrence of preterm labor was revealed: a history of 2 or more medical abortions (OR 5.09), inflammatory diseases of the pelvic organs (OR 3.15), menstrual disorders (OR 3.38), and arterial hypertension (OR 2,4), MARS (OR 2,07), varicose veins disease (OR 3,08), cervico-vaginal infection (OR 5,33), other infectious and inflammatory diseases (OR 9,2).